Lineamenti di una bioetica secondo san Tommaso d’Aquino - Pascual, Fernando (Alpha omega, 2012)
In order to understand what Thomas Aquinas is able to say in respect of Bioethics, the article begins by presenting his view regarding man’s position in the cosmos .Then, it studies the problem of the critical moments in the existence of every human being: its beginning and its end. Afterwards, it studies the Thomistic view of ethics, and our general obligations towards life are made clear. Then follow a few reflections on some key bioethical concepts (health, sickness, medicine) and on several applications to issues like contraception, abortion, homicide and suicide. At the end the article attempts to draw up an overall assessment of the innovative contributions that Thomas Aquinas has to offer to bioethical discussions today and in the future.